1988
DOI: 10.1159/000118485
|View full text |Cite
|
Sign up to set email alerts
|

Fengabine, a New GABAmimetic Agent in the Treatment of Depressive Disorders: An Overview of Six Double-Blind Studies versus Tricyclics

Abstract: Fengabine is a new GABAmimetic compound active in animal models predictive of antidepressant activity. The present overview reports the results of 6 double-blind trials versus tricyclics (TCAs) (3 in outpatients and 3 in inpatients). Overall, 398 adult patients (149 males and 249 females) were treated; 194 with fengabine and 204 with TCAs (98 clomipramine, 63 amitriptyline and 43 imipramine). 284 suffered from major depression (MD) (including major depressive disorder and bipolar disorder, depressed; DSM III) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Increased GABA A /benzodiazepine binding sites were also documented, implying that the decreased GABA activity caused the binding sites to be increased as an outcome of an adaptive mechanism [5,6]. It is also well-known that GABA agonists have anti-depressant effects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Increased GABA A /benzodiazepine binding sites were also documented, implying that the decreased GABA activity caused the binding sites to be increased as an outcome of an adaptive mechanism [5,6]. It is also well-known that GABA agonists have anti-depressant effects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Improvement on fengabine has been reported in a number of open studies (Musch, 1986) with some suggestion of early response. Several double-blind comparisons with tricyclic antidepressants have not shown significant differences up to 4 weeks (Magni et al, 1988;Morselli et al, 1989). No placebo-controlled study of either drug has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Initial pharmacokinetic studies showed it to be well tolerated in doses up to 1200 mg daily. Several open studies, one doubleblind comparison with tricyclics, have suggested that it is an antidepressant in humans (Musch, 1986;Magni et al, 1988;Morselli et al, 1989). However, open studies can provide only preliminary suggestive data, and no placebo-controlled trials of GABA agonists in depression have so far been reported.…”
Section: Introductionmentioning
confidence: 99%
“…(Scheme 20) [195][196]. Fengabine (239) is also a Schiff base and acts as an [121,168] 216 [121,168] 217 [121,168] 222 [163] 223 [163] 218 [163] 224 [163] 225 [163] 219 [163] O O S NH [197][198][199][200].…”
Section: Schiff Bases As Gabamimeticsmentioning
confidence: 99%